2008
DOI: 10.2174/138620708783744543
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Display and High Throughput Screening

Abstract: Retroviruses distinguish themselves from all other mammalian viruses by their abilities to infect and propagate in mammalian cells without causing a cytopathic effect and to stably integrate their genetic information into the genome of the host cell. These unique properties make them an ideal platform for the display and directed evolution of proteins in a mammalian cell environment. This review will describe the essentials about retrovirus biology and then discuss in detail display and screening strategies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…About 80–88% of ligands can be expressed in bacteria and purified as active ligands without problems in protein folding or posttranslational modifications. Glycosylation is important to VEGF secretion but not its functional activity (Buchholz et al, 2008). Even Scg3 with putative glycosylation (Holthuis et al, 1996; Rong et al, 2002), probably in the nonreceptor-binding domain, can be identified by ligandomics in this study.…”
Section: Discussionmentioning
confidence: 99%
“…About 80–88% of ligands can be expressed in bacteria and purified as active ligands without problems in protein folding or posttranslational modifications. Glycosylation is important to VEGF secretion but not its functional activity (Buchholz et al, 2008). Even Scg3 with putative glycosylation (Holthuis et al, 1996; Rong et al, 2002), probably in the nonreceptor-binding domain, can be identified by ligandomics in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages are the flexibility, speed, and controllable modification conditions [106][107][108]. Unfortunately, the effectiveness of the chemically modified particles strongly depended on the reaction conditions of the applied modifications [109,110]. A final strategy to generate APC targeted LVs is based on the fact that binding and fusion functions of LVs can be separated over two distinct glycoproteins.…”
Section: Cell Entry Basedmentioning
confidence: 99%
“…Fortunately, protein eat‐me signals should far outnumber non‐protein eat‐me signals based on our current knowledge (Lauber et al, 2004; Ravichandran and Lorenz, 2007). The incapacity to identify carbohydrate moieties could be addressed by combining ORF strategy with a mammalian display systems, such as retroviral display (Buchholz et al, 2008) and mammalian cell display (Ho and Pastan, 2009), which are less efficient and technically more complicated than ORF phage display.…”
Section: How To Systematically Unravel the Mystery Of Molecular Phagomentioning
confidence: 99%